(untitled) (Balneo and PRM Research Journal, 2025)
Osteoarthritis (OA) is a degenerative joint disease that is typically associated with weight-bearing joints, such as the hips and knees, and is defined by the progressive deterioration of cartilage. The effective treatment of OA is contingent upon the accurate assessment of its clinical and psychological effects. In the present work, we aim to compile the most recent evidence regarding the clinimetric and psychometric evaluations of OA, with a particular emphasis on the hip and knee, a topic still insufficient approached. The WOMAC and KOOS are among the clinimetric instruments that offer valuable insights into physical function, stiffness, and pain. By integrating clinimetric and psychometric tools, a comprehensive approach to managing OA is provided, which identifies both physical and mental health need. The significance of these combined evaluations in enhancing treatment adherence and improving patient outcomes is underscored by the present review. Moreover, treatment and recovery options still have limitations that need to be addressed. Additional research is required to elucidate the psychometric properties of quality-of-life measures and postural control assessments. Future research should concentrate on the development of more comprehensive and robust tools that assess all facets of OA, thereby facilitating personalized interventions that address the multifaceted character of this debilitating disease.